COMPARISON RESULT OF DEM GENERATED FROM ASTER STEREO DATA AND SRTM - Bambang Trisakti; Ita Carolita (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2007)
This paper explains a method to generated DEM (Digital Elevation Model) from ASTER (Advanced Spaceborn Thermal Emission and Reflection Radiometer) stereo data and evaluates the generation of ASTER DEM and SRTM (Shuttle Radar Topography Mission) DEM with 90 m spatial resolution. ASTER DEM is generated from 3n (nadir looking) and 3b (backward looking) level 1b, with 10 ground control points (XYZ coordinate)derived from ASTER RGB 321 geometric-corrected image and SRTM DEM. Almost all tie points are collected automatically and several tie points is added manually. The triangulation and DEM extraction process are made automatically using ERDAS Imagine Software. DEM evaluation is carried out by comparing between ASTER DEM and SRTM DEM in the height distribution of vertical and horizontal transect lines and the height value of the whole DEM image. The process is continued by analyzing the height differences between ASTER DEM and SRTM DEM. The results shows thatASTER DEM has 15 m spatial resolution with height differnces less than 30 m for about 67 percent of total area, and absolute mean error is 27 m (compared with SRTM DEM) This absolute mean error is large enough, because the GCPs (Ground Control Point) used in this study are only in a small amount and most of study area is in the high terrain area (mountainous area) with dense vegetation coverage. Keyword: DEM, ASTER, height difference, GCP.